PENENTUAN EFISIENSI KOLEKTOR PELAT DATAR DENGAN PENUTUP KACA PADA SISTEM PEMANAS AIR SURYA - Zelviana '; Maksi Ginting; Sugianto ' (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
A  research has been conducted to determine the efficiency of flat plate collector  with  its cover  made from  glass. Solar water heaters  were  made  and  comprised of five essential components, namely a  protective box,  a  plate absorbent,  an  insulator,  an  iron pipe, and a  transparent cover. In this study, the water  was flown  into the water tank, through  a  collector, and then  the  water  flowed  into a  tube  collectors.  The  collectors  used  in this  study  were  flat plate  collectors  with one and two layer lid.  The  data  was  collected  within 14 days,  starting from  9.00 am until  3.00 pm  WIB  with one hour time interval.  The average  efficiency  for  a single  layer collector  was  42.62 % to 62.14 % , and for the two layer collectors  was  51.69 % to 85.74 % . These results  showed that the loss of heat on a flat plate collector with two layer was smaller than those of a single layer collector.